Evaluation of the Biosorption Capacity of Saccharomyces cerevisiae for Heavy Metals in Milk - Masoud , R.; Mirmohammad-Makki, F.; Zoghi , A. (Emerging Challenges in Agriculture and Food Science Vol. 5, 2022)
The application of biosorbents like bacteria, yeast, and algae is a biotechnological method for eliminating heavy metals from the environment. These microorganisms can also be used for the decontamination of heavy metals in food and water. Our research team has investigated the heavy metals biosorption in milk by using Saccharomyces cerevisiae. In this regard, initial heavy metals (Pb, Cd and Hg) and S. cerevisiae were added to milk and the bioremoval process was monitored during four days. The objective of this study is to evaluate the effect of some variables including exposure time, temperature, S. cerevisiae concentration and initial metal concentration in the heavy metals (Pb, Cd and Hg) bioremoval process in milk. The analysis of ANOVA showed that among the above the variables, S. cerevisiae concentration, initial metal concentration, and exposure time were statistically significantly associated with heavy metals removal (p values \(≤\) 0.05). The highest biosorption (70%) was observed after 4 days with 30×108 CFU S. cerevisiae in milk. These findings provided further evidence for S. cerevisiae as a powerful biosorbent for heavy metals removal from milk and a potentially safe and green tool for providing safe and healthy food supply.